Pathologic Study of Paraspinal Muscles in Different Types of Scoliosis - Ebrahim Ameri; Hamid Behtash; Bahram Mobini; Behshad Bouzari; Tina Shooshtarizadeh; Payam Kabiri (مجله دانشکده پزشکی اصفهان, 2008)
Background: